Comparing Computational Thinking in Scratch and Non-Scratch Web Design Projects: A MetaAnalysis on Framing and Refactoring - Lee, Chien Sing *; Wong, Daniel K. (Asia-Pacific Society for Computers in Education, 2021)
Development of computational thinking (CT) covers a broad range of skills, as exemplified by diverse CT definitions and assessments. There are however, less research on developing computational perspectives. We aim to investigate how to develop computational perspectives, critical to creativity and innovation, within the Interest-Driven Creator (IDC) theory, which espouses constructivist/constructionist tenets. This paper reviews the foundational works on design thinking, computational thinking and creativity. We then analyse examples in computing and information systems, and one in the creative industries, to derive pedagogical-socio-technological insights. We find that non-Scratch projects, will benefit from framing, via diverse human-computer interaction (HCI) design grand challenges and task refactoring. We also find that designing based on goal-based scenarios, and strategic knowledge, with scalability and extensibility in mind, e.g., via Alexandrian architectural patterns, and logical flow of information, will extend association to aggregation (abstraction). This is followed by refactoring and/or permutations at different levels of granularity. We also find that Scratch’s diversity and underlying design thinking-CT/data science-participatory knowledge management design are critical to non-Scratch CT projects’ success.